Gambaran Tingkat Risiko Jatuh dan Penanganannya pada Pasien Jiwa di Rumah Sakit - Tiara Sas Dhewanti; Intansari Nurjannah (Jurnal Keperawatan Klinis dan Komunitas (Clinical and Community Nursing Journal), 2017)
Background: One of the concerns associated with patient safety is prevention of falls. Patients with mental disorders have a higher risk of falling compared to other patient age, diagnosis of depression, use of antipsychotics medication, and medical therapy management of Electro Convulsive Therapy.Objective: This study was aimed to explore the description of risk for fall levels in the category of psychiatric patients and to identify risk for falls management of mental health patients based on Client Categorization System.Method: A descriptive quantitative research with case study design was performed on 20 psychiatric patients and 4 nurses. The instruments used were Edmonson Fall Risk Assessment Tool (EFRAT) to identify the risk for falls on patients, and Client Categorization System (CCS) to categorize the psychiatric patients. The univariate analysis was used to accomplish the aim of the study.Result: As much as 37,5% patients have risk for falls. The risk of falling level of psychiatric patients occurred mostly on respondents with crisis category (66,7%). No patients with health promotion category have risk for falls. The most activity done with the Nursing Intervention Classification (NIC) (environment modification is using safety equipment. Meanwhile, the most activities done on NIC fall prevention are preparing an appropriate lighting and collaborate with other medical team. Moreover collaboration with other medical team is also needed.Conclusions: Risk for falls on patients with mental health disorders can be found on patients with these category: crisis, acute, and maintenance. Management of patients with mental disorders based in NIC are Fall Prevention and Environmental Modification. ABSTRAKLatar belakang: Pencegahan jatuh merupakan bagian dari keselamatan pasien. Pasien dengan gangguan jiwa mempunyai risiko jatuh lebih tinggi karena usia, diagnosis depresi, penggunaan obat anti psikotik, dan penatalaksanaan terapi medis electro convulsive therapy.Tujuan: Mengetahui gambaran tingkat risiko jatuh dan manajemen penanganannya pada pasien gangguan jiwa beradasarkan Client Categorization System(CCS).Metode: Penelitian ini adalah penelitian deskriptif kuantitatif dengan rancangan case study. Responden terdiri dari 20 pasien gangguan jiwa dan 4 perawat. Instrumen yang digunakan adalah Edmonson Fall Risk Assessment Tool (EFRAT) untuk mengkaji risiko jatuh pada pasien. Sementara, pengkategorian pasien jiwa  dilakukan  menggunakan  instrumen Client  Categorization  System (CCS).  Data  hasil  penelitian dianalisis menggunakan analisis univariat.Hasil: Hasil penelitian didapatkan sebanyak 37,5% pasien memiliki risiko jatuh. Risiko jatuh pada pasien gangguan  jiwa  paling  banyak  terjadi  pada  responden  dengan  kategori  krisis  (66,67%). Pasien  dengan kategori health  promotion tidak  ada  yang  memiliki  risiko  jatuh.  Aktivitas  paling  banyak  dilakukan  pada Nursing   Intervention   Classification (NIC):   Modifikasi lingkungan   adalah   menggunakan   peralatan perlindungan, sedangkan aktivitas pada NIC: Pencegahan jatuh yang selalu dilakukan adalah: identifikasi perpindahan pasien,  menyediakan  pencahayaan  yang  cukup  dan  berkolaborasi  dengan  anggota  tim kesehatan lainKesimpulan: risiko jatuh pada pasien gangguan jiwa dapat terjadi pada pasien dengan kategori krisis, akut, dan maintenance. Manajemen  penanganan  pada  pasien  gangguan  jiwa  berdasarkan  NIC  adalah pencegahan jatuh dan manajemen lingkungan.